Kepemimpinan Kepala Sekolah dan Lingkungan Sekolah terhadap Kinerja Guru - Yulita Elly; Joice Soraya (Jurnal Penelitian dan Pendidikan IPS, 2020)
The problem discussed in this study is the Effect of Principal Leadership and School Environment on the Performance of Taniwel State Vocational School Teachers. This study aims (1) To determine the effect of school principal leadership on teacher performance in SMK Negeri Taniwel; (2) To determine the effect of the school environment on the performance of teachers in Taniwel State Vocational School; and (3) To find out the influence of school principals leadership and school environment together on the performance of Taniwel State Vocational School Teachers. The data collection method used is the survey method type Ex post facto by distributing questionnaires (questionnaire) to teachers who have tested the reliability validity and in accordance with the research conducted. Analysis of the data used by using descriptive analysis, Linearity Test, Multicollinearity Test, T-Test, and F-Test. The results showed that (2) Headmaster's leadership had a positive and partially significant effect on Teacher Performance; (3) School environment has a positive and partially significant effect on Teacher Performance; and (4) Principal's Leadership and School Environment have a positive and significant effect simultaneously on the performance of Taniwel State Vocational School Teachers.